Pengembangan Kristo Rai sebagai Wisata Alternatif di Area Branca Timor Leste - I Made Mardika; Ni Luh Made Mahendrawati; Anak Agung Ayu Dewi Larantika; Ni Made Jaya Senastri; I Ketut Kasta Arya Wijaya; Leonito Reiro; Mateus Ximenes (Postgraduated Community Service Journal, 2025)
Timor Leste is currently developing the tourism sector to support the national economy. One of the tourism potentials being developed is the Branca Area, particularly the Kristo Rei statue, which has not developed as expected since its construction in 2000. In this regard, the Warmadewa University Team, in collaboration with DAPAZ University and the Timor Leste Institute of Business (IOB), implemented a Community Service (PKM) program with the topic "Developing Alternative Tourism in the Branca Area in Timor Leste." The program's primary target group was community leaders from Mateaut Village, the Dili Regency tourism agency, and local tourism operators. The partners' primary challenges related to tourism governance and environmental management, particularly the lack of accessible tourism information for tourists, the suboptimal operation of the tourism information center, and the lack of community awareness as hosts in tourism services. Solutions offered included the development of brochures/leaflets, training of tourism information center staff, and the formation of Tourism Awareness Groups (Pokdarwis). This program successfully increased access to tourism information, empowered tourism information centers, and raised community awareness in serving tourists. The output of this activity is optimizing the tourism potential of Kristo Rei as an alternative tourism destination that directly contributes to the local economy and community well-being.